Role of hydrogen bonding in cocrystals and coamorphous solids: indapamide as a case study - Allu, Suryanarayana; Suresh, Kuthuru; Bolla, Geetha; Mannava, M. K. Chaitanya; Nangia, Ashwini (Crystengcomm, 2019)
The stronger sulfonamide-pyridine (SO2NH2 center dot center dot center dot N-Py) and sulfonamide-carboxamide (SO2NH2 center dot center dot center dot O = C-NH) hydrogen bonds direct the formation of cocrystals, while the weaker sulfonamide-amine (SO2NH2 center dot center dot center dot N-H) hydrogen bond results in coamorphous products. IDP-PIP and IDP-ARG coamorphous solids exhibit remarkable stability under accelerated conditions.